Conflitti di interessi e corruzione: annotazioni sparse sul nuovo assetto normativo previsto dal Motu proprio su “trasparenza, controllo e concorrenza nelle procedure di aggiudicazione” (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Breve premessa – 2. Le rationes che hanno portato alla cristallizzazione di una normativa anti-corruzione e all’implementazione della Convenzione di Merida – 3. I principi fondamentali del nuovo Motu proprio – 4. La nozione di conflitto di interesse e strumenti “preventivi” – 5. Segue. Le cause di incompatibilità – 6. Le tipologie di procedure aggiudicatorie e documentazione – 7. L’esecuzione del contratto oggetto della procedura di aggiudicazione: risvolti civilistici – 8. La lotta alla corruzione – 9. I rimedi giurisdizionali previsti.ABSTRACT: This contribution expresses the first notes on the fight against corruption, but even before the fight against conflicts of interest in the Vatican City State and the Holy See a few days after the adoption of the Apostolic Letter in the form of a Motu Proprio adopted by the Supreme Pope Francis for transparency, control and competition in award procedures. Far from wanting to be a decisive contribution, given the novelty of the discipline, surely the paper investigates the reasons that led to the adoption of such legislation, the founding principles that must permeate the entire discipline, the different types of award procedures and the “preventive” tools set as a “bulwark” of the fight against corruption and, even before, its so-called phase “prodromal”, represented by conflicts of interest. The contribution also focuses on the exquisitely civil aspects (good faith, correctness, exactness of the fulfillment) regarding the execution of the contract to be awarded and on the procedural aspects.